Recognition System Of The Al Qur’an Surah Al-Falaq Verse 1-5 Through Voice Using Ada-Boost - Diauddin Ismail (International Journal of Engineering, Science and Information Technology, 2021)
In everyday life, it is not uncommon when we hear the sound of chanting the holy verses of the Al Al Qur’an  which are read in mosques before prayer time or in other conditions we seem interested in knowing what Surah and which verse is being recited. This is due to the love of Muslims themselves for the Al Qur’an  but not all Muslims memorize the entire contents of the Al Qur’an . Based on the limitations and the magnitude of curiosity about Surah and Verse information, the writer is interested in developing a computer system that can recognize and provide information on the recited Surah and Verse. Advances in computer technology not only make it easier for humans to carry out activities. One of the human intelligences that are planted into computer technology is to recognize the verses of the Al Al Qur’an  Surah Al-Falaq through voice. Ada-Boost method is one method to identify or recognize voice classification, and by using this method the success rate in recognizing verse numbers reaches 72%. This system can only recognize the number of verses of the Al Al Qur’an  Surah Al-Falaq, recorded sound files with the .wav file extension and built using the Delphi programming language.